Seagrass growth at different turbidity levels - Eka Lisdayanti; Rohani Ambo Rappe; Nenni Asriani; Nur Tri Handayani; Steven Rante Limbong (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Seagrass beds are highly productive ecosystems and have ecosystem services in the coastal zone but are continuously declining globally. Mainly due to anthropogenic activities that reduce the amount of light entering the waters and reaching seagrasses, such as dredging, reclamation, sedimentation, and eutrophication. This research was conducted to determine the relationship between turbidity level and seagrass composition and morphology. The observations were conducted in November 2016 in Pangkep district on Sagara Island and Makassar City on Barrang Lompo and Lae-lae Island, South Sulawesi Province. The observation stations are determined based on the level of turbidity conditions. Sagara Island, Barrang Lompo, and Lae-lae are areas that are considered to represent turbid waters, by laying a line transect (roll meter) perpendicular to the coast and doing it 3 times. The data collected in this study related to seagrass conditions such as seagrass composition and seagrass morphometrics. Variables observed in seagrass leaf morphometric observations were leaf surface area and leaf width, leaf thickness, and distance between internodes. In addition, other data collected is environmental parameter data, such as currents, TSS, PAR, temperature, and salinity. One-way ANOVA analysis showed that there was a difference in turbidity levels between Barrang Lompo Island, Sagara Island, and Lae-lae Island with a significance value of 0.000. The types of seagrasses found on Barrang Lompo with light availability of 1735.23 mol/m/s are Enhalus acoroides, Cymodocea rotundata, Halodule uninervis, Halophila ovalis, Thalassia hemprichii. On P. Sagara with light availability of 170.01 mol/m/s, E. acoroides, T. hemprichii, Cymodocea serrulata, H. uninervis, and H. ovalis were found. Whereas in P. Lae-lae only E. acoroides was found. The results showed that the level of turbidity has an influence on seagrass morphometrics, namely leaf ratio and leaf thickness of E. acoroides species, and internode distance in H. uninervis species.Keywords:Availability of lightMorphometricsPARSeagrass bedsTurbidity